2014
DOI: 10.1002/meet.2014.14505101047
|View full text |Cite
|
Sign up to set email alerts
|

Scholar‐built collections: A study of user requirements for research in large‐scale digital libraries

Abstract: To realize the great potential value of large‐scale digital libraries, we need a fuller understanding of the range of ways in which scholarly communities conduct research, or want to conduct research within them. Scholars build collections in the course of their work. How can we anticipate and support various kinds of collection‐building and ‐use, in order to support the diversity of researchers who work in libraries of digital books? This paper reports selected results of a study of how potential user groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…However, Fenlon et al [5] have shown that scholars want the ability to incorporate external metadata and external digital objects within their worksets. Thus, there is a need for resource manipulation at an "extra-DL" level, to remove these single-DL constraints and to fashion worksets drawing from multiple sources, leveraging external metadata and including external resources.…”
Section: Objective 1: Extra-dl Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Fenlon et al [5] have shown that scholars want the ability to incorporate external metadata and external digital objects within their worksets. Thus, there is a need for resource manipulation at an "extra-DL" level, to remove these single-DL constraints and to fashion worksets drawing from multiple sources, leveraging external metadata and including external resources.…”
Section: Objective 1: Extra-dl Resourcesmentioning
confidence: 99%
“…These properties might be identified through computational analysis of item metadata and content, creating further metadata exposed, in turn, as criteria for forming and refining subsequent worksets. Interviews and surveys of HTRC's scholarly users [5] suggest that scholars desire a greater choice in the granularity of objects and object-metadata than is offered natively by a particular DL. For example, the default unit of granularity in the HathiTrust DL is the digitized volume; users express a preference for examining resources at the level of chapters, articles, individual pages or other textual divisions.…”
Section: Objective 2: Intra-item Propertiesmentioning
confidence: 99%
“…The primary distinction that we needed to showcase is that while every research collection is a curated collection, not every curated collection is fit for research (i.e., not every curated collection was curated with the express purpose of answering one or more research questions). 5 With this understanding we developed the following definition, D3. D3: 'If and only if something, x, has been gathered into some curated collection, y, for the purposes of some research motivation, z, then that curated collection, y, is a research collection.'…”
Section: Formal Definitions For Collectionsmentioning
confidence: 99%
“…Our future work includes continuing to analyze methodologies for asserting what kinds of things have been gathered into the worksets. As alluded to above, we have a large number of use cases stating that the granularity of things that can be gathered into worksets needs to be as fine as possible [5], to the point that a workset may comprise individual poems, paragraphs, or even smaller tokens. Similarly, there is a great deal of desire on the part of scholars to gather together resources from different corpuses, reuse data products, and even exploit intermediary results from cleaning algorithms.…”
Section: Additional Features and Future Workmentioning
confidence: 99%
See 1 more Smart Citation